Contrast‐Enhanced Ultrasound Appearance of Hypervirulent Klebsiella pneumoniae Liver Abscesses. (5th February 2020) - Whang, Gilbert; Harris, Robert D.; Tchelepi, Hisham
Abstract : There has been a paradigm shift with Klebsiella pneumoniae (KP) emerging as the most frequently isolated bacterium in pyogenic liver abscesses in immunocompetent patients. Colonization of this hypervirulent KP strain has led to community‐acquired liver abscesses. Septic seeding to distant sites of the body has been recognized and is strongly associated with diabetes. Contrast‐enhanced computed tomographic features have been described. Grayscale ultrasound (US) features remain inconclusive, with variable US appearances. Here we describe the contrast‐enhanced US features of KP liver abscesses, which correlated with previously described computed tomographic findings. The use of contrast‐enhanced US eliminates the need for radiation exposure.